The Use of Tiktok Application to Enchance Students’ Speaking Skill - Yohana Puspita Dewi (Journal Corner of Education, Linguistics, and Literature, 2023)
E-learning or so-called electronic learning systems, it can be defined as the application of information technology in the world of education through virtual classes. Especially in video-based learning such as Tik Tok. The Tik Tok application is an application to create and share various short videos in vertical format,which is played by everyone in everytime. the TikTok application is very widely used by users, especially students, to upload related daily activities. Therefore, it is necessary to have new variations in the application of interactive and effective learning media in order to influence student learning motivation. This study aims to determine the improvement of students' speaking skills by storytelling about a person, object or place that you want to describe using the TikTok application. The subjects of this study were 36 students of the second semester in STMIK Dian Cipta Cendikia.  This research used qualitative with a qualitative descriptive approach to reveal events that occur during research in English learning or when students tell stories (storytelling) using the TikTok application.